2005
DOI: 10.1093/cercor/bhi035
|View full text |Cite
|
Sign up to set email alerts
|

Visual Mental Imagery Induces Retinotopically Organized Activation of Early Visual Areas

Abstract: There is a long-standing debate as to whether visual mental imagery relies entirely on symbolic (language-like) representations or also relies on depictive (picture-like) representations. We sought to discover whether visual mental imagery could evoke cortical activity with precise visual field topography (retinotopy). Participants received three conditions: the perception condition consisted of a standard retinotopic mapping procedure, where two flickering checkerboard wedges rotated around a central fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
211
4
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(231 citation statements)
references
References 48 publications
13
211
4
3
Order By: Relevance
“…Subjects were not allowed to view the stimuli beforehand, discouraging the use of imagery. Moreover, activation of V1 due to imagery or attention typically occurs only in concert with stronger activation of extrastriate cortex (Kastner et al 1998;Kosslyn and Thompson 2003;Slotnick et al 2005;Somers et al 1999), unlike the deactivation observed here. Disinhibitory mechanisms are inconsistent with the inter-areal correlations that we observed.…”
Section: Discussioncontrasting
confidence: 63%
“…Subjects were not allowed to view the stimuli beforehand, discouraging the use of imagery. Moreover, activation of V1 due to imagery or attention typically occurs only in concert with stronger activation of extrastriate cortex (Kastner et al 1998;Kosslyn and Thompson 2003;Slotnick et al 2005;Somers et al 1999), unlike the deactivation observed here. Disinhibitory mechanisms are inconsistent with the inter-areal correlations that we observed.…”
Section: Discussioncontrasting
confidence: 63%
“…Studies in humans (Krekelberg et al, 2005) and monkeys (Krekelberg et al, 2003) show that the same populations of cells in extrastriate visual areas code for both implied and real motion. Moreover, MT is activated during mental imagery and perception of actual and implied motion (Slotnick et al, 2005). It is possible that mental imagery of forward motion paths (Munger et al, 1999) allows us to fill in the missing visual information and thus to create representational momentum effects.…”
Section: Motor Facilitation and Anticipatory Mental Simulation Of Thementioning
confidence: 99%
“…For example, Slotnick, Thompson, & Kosslyn (2005) showed that when participants are asked to visualize a flickering checkerboard wedge rotating, the retinotopic activation maps, as measured by functional magnetic resonance imaging (fMRI), more closely resemble retinotopic perceptual maps (resulting from actual viewing of the stimuli) than when participants are asked to pay attention to the region of space that would be occupied by the checkerboard.…”
Section: Discussionmentioning
confidence: 99%